Innovative Learning Spaces in the Making - Hughes, Janette Michelle; Morrison, Laura Jane (Frontiers in Education, 2020)
This article details a qualitative, case study focusing on the affordances of innovative makerspaces for teaching and learning. The theoretical perspectives framing the research include embodied learning, materiality, neuroarchitecture and structuralism as it relates to power, inclusion and engagement within a learning space. Findings provide an overview of how the physical space (including the architecture of, and the furniture and materials within, the space) became an actor in the learning process. Three schools are highlighted as the case study examples. A detailed overview is provided of each of the spaces and the findings are supported through rich descriptions and a variety of data sources (i.e. teacher quotes, Twitter posts, images). This study is timely given that many Ontario schools have been and continue to build makerspaces to respond to the need to develop students’ global skills and competencies (critical thinking; innovation and creativity; self-directed learning; collaboration; communication and citizenship).